Equivalent Processing of Self-Relevant Information in Autism: Evidence from the Cocktail Party Phenomenon. - Alikadic, Lejla; Röer, Jan Philipp (Auditory Perception & Cognition, 2025)
The cocktail party phenomenon refers to the finding that approximately one third of the participants detect their own name in the to-be-ignored message during a selective listening task. Here we present a preregistered replication of the cocktail party phenomenon in autism. Previous studies comparing the processing of self-relevant information in neurotypical and autistic individuals yielded mixed results. Some studies showed that the response to one's own name is diminished in autistic individuals, while others found no differences. A systematic investigation of the classic cocktail party phenomenon comparing autistic and neurotypical individuals has not yet been conducted. We used a standard selective listening task in which the task for the participants was to listen to the relevant message presented to their right ear and repeat each word as soon as they hear it while at the same time ignoring the to-be-ignored message presented to their left ear. The to-be-ignored message consisted of short sentences, two of which contained the participant's own name and that of a yoked-control partner, respectively. Replicating the classic finding, 13 of 48 participants in the autistic group (27%) and 18 of 50 participants in the neurotypical group (36%) reported hearing their own name in the to-be-ignored message and those who did made more shadowing errors shortly after the presentation of the name. There were no group differences and name detection was not related to individual differences in the autism-spectrum quotient.